Analisis Equivalent Rate Perbankan Syariah Pada Masa Pandemi (Studi Pada Bank BNI Syariah) - Asiyah, Binti Nur; Islamiah, Cahyani; Ningrum, Christina Ika (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to analyze the mechanism in applying the distribution of profit sharing of third-party funds collected using the equivalent rate. The research uses a case study approach and type. To obtain data, researchers used data on the annual and quarterly financial statements of BNI Syariah Bank in 2020, 2019, and 2018 and literature studies in the form of books and research articles. The study results of the Islamic banks' efforts to increase customer interest, one of which is by using profit sharing ratio information in the form of an equivalent level. The strategy of Bank BNI Syariah to present an equivalent level in its Quarterly Financial Statements is the right step to increase customer interest in placing their funds in BNI Syariah banks. Furthermore, this research shows that the Equivalent rate at BNI Syariah Bank in 2020 in its quarterly report tends to decrease in the pandemic era in line with the national and global economic slowdown.